2012
DOI: 10.5056/jnm.2012.18.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Hyposensitivity

Abstract: Impaired or blunted rectal sensation, termed rectal hyposensitivity (RH), which is defined clinically as elevated sensory thresholds to rectal balloon distension, is associated with disorders of hindgut function, characterised primarily by symptoms of constipation and fecal incontinence. However, its role in symptom generation and the pathogenetic mechanisms underlying the sensory dysfunction remain incompletely understood, although there is evidence that RH may be due to 'primary' disruption of the afferent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 129 publications
(186 reference statements)
0
66
0
1
Order By: Relevance
“…Moreover, it has been suggested that prevalence data may be distorted by men being more unwilling to report fecal incontinence than women. 4,8 Fecal continence is a complex physiological function that involves anatomical and functional integrity of the anal sphincter, anal and rectal sensitivity and intrinsic and extrinsic motor innervation 16 ; fecal consistency also plays a role, given that loose and liquid stools are less easily retained. Fecal incontinence is regarded as a multifactorial condition as it is not usually associated with just one pathogenic abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been suggested that prevalence data may be distorted by men being more unwilling to report fecal incontinence than women. 4,8 Fecal continence is a complex physiological function that involves anatomical and functional integrity of the anal sphincter, anal and rectal sensitivity and intrinsic and extrinsic motor innervation 16 ; fecal consistency also plays a role, given that loose and liquid stools are less easily retained. Fecal incontinence is regarded as a multifactorial condition as it is not usually associated with just one pathogenic abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…While rectal hyposensitivity is often present in constipation (Scott et al, 2011) and regularly in spinal cord injury (Burgell and Scott, 2012), both rectal hypo-and hypersensitivity can be present in irritable bowel syndrome (Mertz et al, 1995). Faecal incontinence patients can present with rectal and anal hyper-or hyposensitivity (Chan et al, 2005;Vasudevan et al, 2007;Burgell and Scott, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Faecal incontinence patients can present with rectal and anal hyper-or hyposensitivity (Chan et al, 2005;Vasudevan et al, 2007;Burgell and Scott, 2012). As in some conditions both hypo-and hypersensitivity may be present, abnormal sensation is often tied to more severe symptoms and affects treatment options, sensitivity testing is an important part of patient evaluation (Burgell and Scott, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial pathophysiological difference may well lie in different visceral sensitivities: colonic hypersensitivity is more common in IBS, and rectal hyposensitivity is more often seen in FC (17)(18)(19).…”
Section: What Similarities and Differences Are There Between Irritablmentioning
confidence: 99%